Pengaruh Motivasi Kerja, Lingkungan Kerja, dan Kepuasan Kerja terhadap Produktivitas Karyawan di PT. Nihon Seiki Indonesia - Santa Clara Putri; Jhonni Sinaga; Supriyanto Supriyanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the influence of Work Motivation, Work Environment, and Job Satisfaction on Employee Productivity at PT. Nihon Seiki Indonesia. This research is motivated by the phenomenon of declining employee productivity as shown by the non-achievement of work targets in recent months. This problem indicates the possibility of a decline in internal quality that needs to be evaluated, such as low motivation, less supportive work environment conditions, and less than optimal job satisfaction. This decline can also have an impact on the company's overall performance, including in terms of efficiency, production quality, and customer satisfaction that are declining over time. The method used in this study is a quantitative method with a descriptive and verifiable approach. The data collection technique was carried out through the distribution of questionnaires to 90 employees as a sample of the total population of 115 employees working in the company. The research instrument was tested through validity and reliability tests. Data were analyzed using multiple linear regression analysis, t-test (partial), F test (simultaneous), and determination coefficient (R²) test, with the help of SPSS software version 26. The results of the study show that Work Motivation, Work Environment, and Job Satisfaction have a significant effect on Employee Productivity, both partially and simultaneously. These findings confirm that the increase in employee work productivity is not only dependent on external factors such as technology and management systems, but is also highly determined by internal factors that are directly related to individual comfort and satisfaction at work. Therefore, company management needs to focus more on efforts to create a conducive work environment, build strong motivation, and increase employee job satisfaction as a strategy to optimize productivity. In addition, continuous training and effective communication between teams also need to be improved to maintain morale, collaboration, and the achievement of overall organizational targets.